“The best men can be”: New configurations of masculinity in the Gillette ad “We believe” - Nebeling Petersen, Michael; Hvidtfeldt, Karen (Kvinder, Køn & Forskning, 2020)
In January 2019, the company Gillette released a short movie “We believe” as advertisement for the brand. In the ad, Gillette reframes their slogan from “the best a man can get” to “the best a man can be.” Connecting the video to the #MeToo movement and critiquing ‘toxic masculinity’, Gillette portrays a new, more responsible, gentle, empathetic masculinity for “the men of tomorrow.” In this article, we present and discuss theories and strands of masculinity studies, and we analyze how the short movie portrays contemporary masculinity vis-à-vis these theories. Our argument is that while Gillette’s short movie and similar branding movies appeal to social responsibility and might open for new and more inclusive masculinities, it does, however, at the same time reproduce the patriarchal organization of masculinity in which power and privilege run from man to man and leave women and children as objects. Furthermore, the recoding of masculinity from toxicity to empathy is framed as an individual choice within neoliberal logics.